1981
DOI: 10.1002/chin.198138010
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: DIFFUSE REFLECTANCE MEASUREMENTS OF MOLYBDENUM TRIOXIDE AND ITS SUBOXIDES

Abstract: Die Messungen werden zwischen 300 und 900 nm für M003, MOI3O38, MO9O26, M0802 , , Mo"O4 , , M0401, und M002 durchgeführt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The UV-visible-near IR absorption spectrum (Fig. S2 †) shows a classical Drüde behavior coherent with the well-known metallic properties of molybdenum dioxide, 21 with additional absorbance between 800 and 2000 nm due to the organic core absorption. Thermogravimetric analysis (not shown) indicates that the material contains 58 wt% of organic products.…”
Section: Core-shell Particles Synthesissupporting
confidence: 63%
See 2 more Smart Citations
“…The UV-visible-near IR absorption spectrum (Fig. S2 †) shows a classical Drüde behavior coherent with the well-known metallic properties of molybdenum dioxide, 21 with additional absorbance between 800 and 2000 nm due to the organic core absorption. Thermogravimetric analysis (not shown) indicates that the material contains 58 wt% of organic products.…”
Section: Core-shell Particles Synthesissupporting
confidence: 63%
“…4,12,19,20 This compound also exhibits a metal-like behavior with low electrical resistivity, which confers fast electrochemical reactions and facilitates electron percolation. [21][22][23] The conductivity of the self-supported material was evaluated to assess its suitability for building electrodes without use of external conductive carbon additive. For that purpose, a cohesive pellet was prepared without calcination in order to prevent sintering and to characterize the assynthesized material.…”
Section: Core-shell Particles Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[23]forW03 oxide. The energy gap in case of M0O3 oxides [24] ranging between M0O3 and M0O2 was found to increase gradually with increasing oxygen deficiency which was proved by other physical properties to correspond to the decrease in the average valency of the metal atom [25], VERNON R. PORTER et al [26] studied the optical spectra of 25 transition metal oxides. They found that the transition energies of the maxima varied logarithmically with the carrier concentration in accordance with MAYER'S rule.…”
Section: Resultsmentioning
confidence: 96%
“…The change of Eg from one value to another may be easily accepted to be due to the Variation in crystal structure of the different phases and/or the oxygen deficiency [23][24][25][26][27]. The astonishing increase in the value for the a-UO3 can be interpreted by the unusual structure.…”
Section: Resultsmentioning
confidence: 99%